Transformative and Engaging Leadership: Lessons from Indigenous African Women - Madimbo, Maggie (Palgrave Macmillan, 2016)
This book explores how spirituality and resiliency defines the character of African women and inspires them to serve the communities and organizations around them. Through portraits of twelve Malawian women national leaders, it celebrates the lives of indigenous women and describes how their unique backgrounds and experiences have contributed to their leadership development. It provides an understanding of the strategies these women employ to move beyond historical barriers to exercise leadership. The author introduces a new leadership model called transformative engaging leadership, which demonstrates how African women leaders use their inner strength to thrive and succeed in the midst of challenges. It contributes to African female leadership studies and will be helpful to leaders and organizations that have a passion for advancing female leaders in the developing world.
Paid